A diachronic study of self-sourced reporting clauses in mechanical engineering and education. - Pan, Fan; Lv, Tianran (Southern African Linguistics & Applied Language Studies, 2025)
Reporting clauses are a powerful way of constructing stance that contributes to writers' presentation of propositions. Based on a corpus of 320 research articles from a hard discipline (mechanical engineering) and a soft discipline (education), this study examined the diachronic changes in the stance construction in self-sourced reporting clauses in research articles from 1970 to 2020, in terms of grammatical subjects, attribution sources and reporting verbs. Results of diachronic analysis displayed somewhat similar changing trends and disciplinary variations in the use of self-sourced reporting clauses. Compared with 1970, writers in both disciplines in 2020 seemed to rely less on it subjects, indicating that writers in 2020 were less likely to fully conceal themselves. Mechanical writers in 2020 were more likely to choose non-human subjects to strengthen the objectivity of research whereas education writers tended to use more human subjects to increase their visibility. In addition, in 2020, mechanical writers preferred to use more show verbs to report factual information and education writers relied more on find verbs to present experiment-based results. These findings hopefully inform academic writing training for novice academic writers.